Studi Fenomenologi: Pencegahan Fraud Pada PT. Permodalan Nasional Madani Ventura Syariah Cabang Makassar - Santiarsi; Nurwanah, Andi; Alam, Roslina (Jurnal Online Manajemen ELPEI, 2025)
The research results show that fraud at PT. Permodalan Nasional Madani Ventura Syariah fraud occurred in the form of side streaming. Side streaming is a form of fraud, namely customers and/or cooperative members using financing funds that are not in accordance with the financing objectives. Completion of side streaming actions at PT. Permodalan Nasional Madani Ventura Syariah is very necessary to avoid other risks such as the risk of financing problems and the risk of sharia compliance. The efforts made by PT. Permodalan Nasional Madani Ventura Syariah in completing side streaming actions is by persuasive means through administrative control. Permodalan Nasional Madani Ventura Syariah is expected to be able to consistently and optimally carry out the monitoring and coaching process for customers so that the quality of the financing carried out is well maintained so that the financing can run smoothly from the beginning of the application until it is completed according to the agreement.